International Conference on Space Optics — ICSO 2020 2021
DOI: 10.1117/12.2600012
|View full text |Cite
|
Sign up to set email alerts
|

Reaching GHz single photon detection rates with HgCdTe avalanche photodiodes detectors

Abstract: In the present communication, the characterization results of an in-house developed four-quadrants detection module based on HgCdTe APDs and a Si-CMOS ROIC pre-amplifier is discussed. The module has been designed to be employed as high data rate ground-segment detector for 1.55 μm long-distance free-space optical communication links in the framework of a project funded by the European Space Agency. The detector is characterized by a multiplication gain in excess of M = 150, a ROIC input referred noise of Ne = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The input referred noise level in photons, estimated by the ratio of the voltage noise and the fast signal amplitude response of the detector, is close to NEPh~100 photons on each channel. This value is higher than the one observed in the previously characterized devices, NEPh~60 photons [8]. The increase noise can be explained by use of different optical coupling in the previously reported measurement, in which the light was focused onto the detector using a lens with a smaller focal distance and without the use of a micro-lens.…”
Section: Methodsmentioning
confidence: 59%
See 3 more Smart Citations
“…The input referred noise level in photons, estimated by the ratio of the voltage noise and the fast signal amplitude response of the detector, is close to NEPh~100 photons on each channel. This value is higher than the one observed in the previously characterized devices, NEPh~60 photons [8]. The increase noise can be explained by use of different optical coupling in the previously reported measurement, in which the light was focused onto the detector using a lens with a smaller focal distance and without the use of a micro-lens.…”
Section: Methodsmentioning
confidence: 59%
“…These measurements have shown that the detectors enables down to single photon detection with a high quantum efficiency and low excess noise at a record high detection rate, in excess of 500 MHz, and with a dark count rate of 500 kHz. These results shows on the strong potential of this technology to detect and process information at a single photon signal level [4], [8].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Overviews of practically achieved RFE sensitivities can be found in [34] on p. 330 and in [35] (Table 3). An even higher sensitivity has been reported by an alternative APD semiconductor material, HgCdTe, and commercial devices for FSO communication applications might soon be demonstrated [36,37].…”
mentioning
confidence: 98%